Knowing what we know : the transmission of knowledge, from ancient wisdom to modern magic - Winchester, Simon (Harper, an imprint of HarperCollinsPublishers, 2023)
Examining such disciplines as education, journalism, encyclopedia creation, museum curation, photography and broadcasting, an award-winning writer explores how humans have attained, stored, and disseminated knowledge.